Forest owners' decision support in voluntary biodiversity-protection projects - Kurttila, Mikko; Leskinen, Pekka; Pykäläinen, Jouni; Ruuskanen, Tiina (Silva Fennica, 2008)
New forest-biodiversity-protection instruments based on temporary protection periods and non-industrial private forest ownersâ voluntary participation have been recently introduced and tested in pilot areas located in Southern Finland. Thanks to their several benefits, the use of voluntary instruments is becoming more common in many other countries as well. Voluntary protection here means that forest owners voluntarily set aside tracts of forest to be protected and define their compensation fees. Depending on the objectives of the forest owners, the compensation fee reflects the forest ownersâ (positive) attitude towards biodiversity, scenic beauty, recreational values and/or the existence of long-term cutting possibilities. When a forest owner decides to offer part of his/her forest holding to be temporarily protected, the owner faces a new decision problem related to definition of the compensation fee, which should be based on diverse information concerning stand- and holding-level opportunity costs as well as on the biodiversity value of the stand. This article introduces three decision-support elements for assisting forest owners in defining their compensation fees. The first element relates to the assessment of the potential stand-level loss of timber harvesting income that the temporary protection of the stand may cause. The second element sets the holding-level opportunity cost of protection by utilizing the forest ownersâ holding level goals, the holdingsâ production possibilities and optimization methods. The third element describes the biodiversity value of the stand by means of a multi-criteria expert model. Case study material collected from the area of Central Karelia Herb-rich Forests Network pilot project is used to illustrate the characteristics of the decision-support elements and to point out some development needs for the future use of these elements.